The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1128/mcb.01030-15
|View full text |Cite
|
Sign up to set email alerts
|

H19 Long Noncoding RNA Regulates Intestinal Epithelial Barrier Function via MicroRNA 675 by Interacting with RNA-Binding Protein HuR

Abstract: The disruption of the intestinal epithelial barrier function occurs commonly in various pathologies, but the exact mechanisms responsible are unclear. The H19 long noncoding RNA (lncRNA) regulates the expression of different genes and has been implicated in human genetic disorders and cancer. Here, we report that H19 plays an important role in controlling the intestinal epithelial barrier function by serving as a precursor for microRNA 675 (miR-675). H19 overexpression increased the cellular abundance of miR-6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
124
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 126 publications
(130 citation statements)
references
References 65 publications
(101 reference statements)
6
124
0
Order By: Relevance
“…To determine the in vivo function of HuRmediated Cdc42 expression in the intestinal epithelium, we used IE-HuR Ϫ/Ϫ mice that we recently generated. As reported previously (19,29), HuR levels in the small intestinal ( Fig. 4A, left) and colonic mucosa (data not shown) were undetectable in IE-HuR Ϫ/Ϫ mice but were at wild-type levels in stomach mucosa, lung, liver, and pancreas.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…To determine the in vivo function of HuRmediated Cdc42 expression in the intestinal epithelium, we used IE-HuR Ϫ/Ϫ mice that we recently generated. As reported previously (19,29), HuR levels in the small intestinal ( Fig. 4A, left) and colonic mucosa (data not shown) were undetectable in IE-HuR Ϫ/Ϫ mice but were at wild-type levels in stomach mucosa, lung, liver, and pancreas.…”
Section: Resultssupporting
confidence: 87%
“…Our previous studies (21,32,33) reveal that HuR stabilizes stim1 mRNA, encoding the Ca 2ϩ sensor protein STIM1 (activator of Ca 2ϩ influx in IECs), and also stimulates translation of the transcription factor MYC, two proteins that critically stimulate IEC migration and proliferation and enhance gut mucosal repair after injury (4,48,49). In support of our current findings, targeted deletion of HuR in IECs decreases the regenerative potential of crypt progenitors in mice exposed to irradiation (29) and represses the recovery of the intestinal barrier function after I/R stress (19). However, the exact roles of RhoB and RhoC in inhibition of intestinal epithelial restitution after injury resulting from HuR deletion remain unclear.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…LncRNA H19 is encoded by a paternally imprinted gene, H19, whose oncogenic functions have been investigated in the context of pancreatic ductal adenocarcinoma, hepatocarcinoma, bladder cancer, glioma and gastric cancer [21-25]. Recent data and studies of miR-675-5p derived from lncRNA H19 indicate that the lncRNA H19/miR-675-5p axis plays a pro-oncologic role by regulating the expression of several target genes [26-30]. …”
Section: Introductionmentioning
confidence: 99%
“…For example, CUGBP1 interacts with miR-222 to inhibit translation of the Cdk4 mRNA synergistically (18), but it competes with HuR to regulate translation of the tight junction occludin and transcription factor MYC antagonistically (25,26). The exact mechanism by which CUGBP1 enhances the association of miR-195 with Igf2r mRNA is unclear at present, but it has been reported that miRNA binding sites are commonly present near RBP binding sites (38,39), suggesting that in some cases RBP and miRNA actions could be enhanced or could compete via their physical interactions with given mRNAs. However, RBPs and coregulatory miRNAs can also bind at locations that are up to several hundreds or thousands of bases apart in some targets (16,40,41).…”
Section: Discussionmentioning
confidence: 99%